Long-Term Outcome of Left Main Percutaneous Coronary Intervention in Patients with Coronary Artery Disease - Marushko, A.; Mankovsky, G.; Marushko, Ye.; Kuzmenko, S.; Rudenko, N. (Ukrainian Journal of Cardiovascular Surgery, 2020)
At the present time, left main (LM) stenting is an alternative to coronary artery bypass grafting in patients with coronary artery disease (CAD) and haemodynamically significant LM lesion. Despite of long history of LM interventions, long-term results are still poorly understood. Presented data are still conflicting and need further affirmation. Aim. To investigate long-term outcomes of percutaneous coronary intervention (PCI) in patients with LM lesions. Materials and methods. The study included 27 patients with CAD with haemodynamically significant LM lesion who underwent PCI. The risk was calculated using the SYNTAX Score and the SYNTAX Score II in all the patients. According to the results of the calculation, patients were divided into 3 groups: the low risk group (SYNTAX Score = 0-22) included 16 (59.3%) patients, the medium risk group (SYNTAX Score = 23-32) included 8 (29.6%) patients, and the high-risk group (SYNTAX Score > 32) included 3 (11.1%) patients. Results. The incidence of major adverse cardiovascular events during the mean follow-up period of 30.9 months was 11.1%, while 89.9% of patients had good immediate and long-term results of the procedure. Fatal cases were reported only in groups of patients with intermediate and high risk according to evaluation by the SYNTAX score. No fatal cases were observed in low risk group of patients according to the SYNTAX score. Thus, patient affiliation with one of the risk groups based on the SYNTAX Score scale affected the long-term LM PCI outcomes. Conclusions. In patients with LM lesion, PCI can be performed with good long-term results in 89.9% of cases. The main criterion for the selection of patients for LM PCI is the risk calculation data based on the SYNTAX Score scale, taking into account the decision of the Heart Team.